Associations of PART1 and DEFB1 polymorphisms with Dental Caries in twelve-year-old children in Southern China: a cross-sectional study - Fei Ma; Haoyu He; Shaoyong Chen; Xueting Yu; Qiulin Liu; Xiaojuan Zeng (BMC, 2023)
Abstract Objective: The aim of this study was to assess associations of PART1 rs27565 and DEFB1 rs11362 polymorphisms with the prevalence of dental caries in twelve-year-old children in Nandan County, Guangxi, China. Methods: A total of 1,061 children were included in this cross-sectional study and divided into two groups based on the Decayed, Missing and Filled teeth (DMFT) index: caries-free children (DMFT score = 0) and children with caries (DMFT score ≥ 1). Demographic characteristics, oral hygiene behaviour and dietary habits were collected through household records and questionnaires. Genomic DNA was extracted from buccal cells, and PART1 rs27565 and DEFB1 rs11362 polymorphisms were genotyped using a custom-designed 48-Plex single nucleotide polymorphism-scan kit. Results: Carriers of the PART1 rs27565 C allele (odds ratio [OR] = 1.338, 95% confidence interval (CI) = 1.015-1.764, P value = 0.039) and carriers of the DEFB1 rs11362 T allele (OR = 1.364, 95% CI = 1.056-1.762, P value = 0.017) had a higher risk of caries. Carriers of the PART1 rs27565 TC or CC genotype who ate sugary food more than once a week had a 1.6-fold higher risk of caries than TT carriers who ate sugary food at most once a week (OR = 1.579, 95% CI = 1.032-2.414, P value = 0.035). Carriers of the DEFB1 rs11362 CT or TT genotype who ate sugary food more than once a week had a 2.1-fold higher risk of caries than CC carriers who ate sugary food at most once a week (OR = 2.057, 95% CI = 1.438-2.940, P value < 0.001). Conclusion: PART1 rs27565 and DEFB1 rs11362 polymorphisms were associated with caries in 12-year-old children in Nandan County, Guangxi, China. Carriers of the PART1 rs27565 TC or CC genotype and the DEFB1 rs11362 CT or TT genotype who ate sugary food more than once a week had a high probability of having caries.